PELAKSANAAN ASUHAN KEBIDANAN KOMPREHENSIF PADA NY. E UMUR 27 TAHUN DI PUSKESMAS SEKAR BIRU KABUPATEN BANGKA BARAT - Astri Yulia Sari Lubis; Ashar Abilowo (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2023)
The process of pregnancy, childbirth, postpartum, and having a baby is a physiological thing for every woman. Complications of pregnancy could be happened in the form of mild or severe complications that can cause pain, disability, and even death for both mother and baby. For this reason, pregnant women are recommended to carry out antenatal care or pregnancy check at least 6 times. The aim of this Final Project was to provide comprehensive midwifery care starting from pregnancy, childbirth, newborns, and family planning using SOAP documentation. This study was conducted in February-April 2022 using data collection methods through interviews and observations. The midwifery care provided to Mrs. E includes pregnancy check-ups 2 times, delivery once, postpartum and newborn visits 4 times, and family planning counseling once. At 38 weeks 5 days of gestation, Mrs. E gave birth at the Sekar Biru health center with a normal delivery. Mrs. E’s baby was born spontaneously and immediately cried with male quality and birth weight 3100 grams and birth length 50 cm. when the baby was a week old, Mrs. E turned out to have given formula milk as an alternative to breast milk. Based on research that has been done, it can be concluded that there are some gaps between theory and practice . Therefore, students are expected to continue to apply quality midwifery care management in order to become competent and qualified health workers.